Perspective: The Lung, Particles, Fibers, Nanomaterials, and Autoimmunity - Pollard, K. Michael (Frontiers in Immunology, 2020)
Studies have shown that a wide range of factors including drugs, chemicals, microbes, and other environmental agents can induce pre-clinical autoimmunity. However, only a few have been confidently linked to autoimmune diseases. Among these are exposures to inhaled particulates that are known to be associated with autoimmune diseases such as lupus and rheumatoid arthritis. In this article, mechanisms of particle, fiber and nanomaterial induction of autoimmunity are discussed with a focus on the importance of pulmonary inflammation and the development of persistent adaptive immunity. It is hypothesized that inhalation of particulate material known to be associated with human autoimmune diseases, such as cigarette smoke and crystalline silica, results in a complex interplay of a number of pathological processes, including, toxicity, oxidative stress, cell and tissue damage, chronic inflammation, post-translational modification of self-antigens, and the formation of lymphoid follicles that provide a milieu for the accumulation of autoreactive B and T cells necessary for the development and persistence of autoimmune responses. This procession of events provides a foundation from which to pursue experimental studies to determine the potential of other particles and fibers to induce autoimmunity. Such studies will provide a more detailed understanding of the physical and chemical properties of particulate matter that lead to the initiation and propagation of harmful innate and adaptive immunity in the lungs.